Ekeland sequences compact in L∞ - Lucio Boccardo (Rendiconti di Matematica e delle Sue Applicazioni, 2016)
In this paper we use Ekeland's ε-variational principle and we prove that, for some integral functionals, there exists a minimizing sequence compact in L∞.